2018
DOI: 10.1063/1.5009980
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of intermolecular interactions in α-glycine under high pressure

Abstract: Pressure-response on the crystal structure of deuterated α-glycine was investigated at room temperature, using powder and single-crystal X-ray diffraction, and powder neutron diffraction measurements under high pressure. No phase change was observed up to 8.7 GPa, although anisotropy of the lattice compressibility was found. No significant changes in the compressibility and the intramolecular distance between non-deuterated α-glycine and deuterated α-glycine were observed. Neutron diffraction measurements indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 65 publications
3
12
0
Order By: Relevance
“…3 The crystal structure has been determined by X-ray single-crystal and neutron powder diffraction at 6.2 (ref. 4) and 6.4 GPa, 5 respectively. Very recent angle-dispersive X-ray diffraction measurements show that the phase persists to 50 GPa.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…3 The crystal structure has been determined by X-ray single-crystal and neutron powder diffraction at 6.2 (ref. 4) and 6.4 GPa, 5 respectively. Very recent angle-dispersive X-ray diffraction measurements show that the phase persists to 50 GPa.…”
Section: Introductionmentioning
confidence: 92%
“…There is a single-crystal to single-crystal phase transition at 18.2 GPa which reduces the space group symmetry from P2 1 2 1 2 1 , to P2 1 , though the unit cell metrics are similar either side of the transition. The structure was modelled with a twofold axis about a as a twin law, but the twin fraction refined to 0.05 (5). The orthorhombic cells of the structure below 18.2 GPa were placed in a non-standard setting to match that of the monoclinic phase in order to facilitate comparisons between phases.…”
Section: Structure Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…It was also found that the double-well potential of a hydrogen bond is transformed into a single well under pressure. A neutron diffraction study of deuterated -glycine up to 8.7 GPa (Shinozaki et al, 2018) showed non-uniform changes of hydrogen bonds on weak interactions in crystals compression, with a large shrinking of bifurcated N-DÁ Á ÁO and C-DÁ Á ÁO bonds, while strong linear N-DÁ Á ÁO bonds change little and in both senses, but in any case, Hirshfeld analysis revealed that the compression was due mainly to squeezing out of voids rather than shrinkage of these bonds. Fanetti et al (2018) analysed the role of (classical) hydrogen bonds under pressure, in favouring or hindering solid-state reactions (e.g.…”
Section: Non-standard Conditionsmentioning
confidence: 99%
“…High pressure is one method which can be used to regulate and control the electronic structure and optical properties of many materials. [4][5][6]12,24,26,27,30,31,36,37 From previous observations, pressure has been shown to drastically alter the properties of amino acids, and can induce phase transitions. 13,32 Thus, crystal structures that experience high pressures may result in sufficiently different, and potentially applicable changes in their optical and electronic properties.…”
Section: Introductionmentioning
confidence: 99%